Challenges and opportunities for research clinicians interested in pain: results of a survey - Siddons, Andrew; Wandner, Laura Dover; Porter, Linda L. (Frontiers in Pain Research, 2023)
The National Institutes of Health and its independent advisors recognize the need to develop a strong pain research workforce and provide opportunities, particularly for clinicians, to pursue research careers. A survey was conducted to better understand the challenges facing the clinical pain research community. Respondents reported that time and funding to pursue research were the most critical factors either enabling or holding them back from a research career. Respondents who received some kind of formal research training or mentorship were more likely than those who did not to have federal research funding and to be at more advanced stages of their careers. The findings point to a need for all stakeholders in the pain research community to help formalize research training and provide funding or protected time to support the ambitions of aspiring researchers.